Strategies for Enhancing the Pedagogical Competence of Special Education Teacher Candidates in Early Reading Instruction for Hearing-Impaired Students - Mursita, Rohmah Ageng; Winarsih, Murni; Bintoro, Totok; Manar, Mayasari; Alamsyah, Rafli (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
The acquisition of foundational literacy skills presents a critical challenge for students with hearing impairments, a difficulty often exacerbated by teacher preparation programs that neglect the specialized training necessary for practical competency. This study aims to bridge this pedagogical gap by exploring and validating specialized instructional strategies designed to strengthen the competence of prospective special education teachers in delivering effective early literacy instruction. Utilizing a qualitative descriptive design, the investigation involved six prospective teachers from Universitas Negeri Jakarta and ten hearing-impaired students. Data triangulation was employed through systematic classroom observations, semi-structured interviews, literacy assessments, and the analysis of teaching artifacts. Findings reveal substantial advancements in both educator competence and student outcomes; specifically, teacher candidates demonstrated a 60% increase in teaching confidence and a notable 140% improvement in applying Total Communication and Reflective Maternal Methods (RMM). These pedagogical shifts correlated with significant student achievements, evidenced by a 100% to 200% increase in vocabulary acquisition, alongside enhanced alphabetic recognition and decoding skills. The novelty of this research lies in identifying the vital correlation between emotional scaffolding via RMM and lexical expansion, positioning emotional connection as a critical psychological dimension in special education pedagogy. Additionally, it contributes a validated multimodal framework integrating visual phonics and sound-rhythm perception to bridge auditory gaps. Directly supporting Sustainable Development Goal (SDG) 4, this study addresses the identified pedagogical deficit by demonstrating that integrating evidence-based, multimodal methodologies into teacher preparation significantly enhances instructional quality. Consequently, it advocates for curriculum reforms to ensure equitable, quality education for students with hearing impairments.